Pengaruh Konsentrasi Ragi Rhizopus oligosporus DP02 Bali Terhadap Karakteristik Tempe Kacang Gude (Cajanus cajan (L) Millsp) - Nathania Saraswati, Anisha; Duniaji, Agus Selamet; Trisna Darmayanti, Luh Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 1 (2023): Jurnal ITEPA, 2023)
The research was conducted with the aims to determine the effect of mold concentration with Rhizopus oligosporus DP02 Bali on the characteristic of pigeon peas tempeh and to determine the appropriate yeast concentration to produce tempeh with the best characteristic. The experimental design that used in this research was a completely randomized design with the treatment consisting of 5 levels of mold concentration, namely: 1%, 2%, 3%, 4%, and 5%. Each treatment was repeated 3 times to obtain 15 experimental units. The data were analyzed by analysis of variance and if there was a significant effect, the Duncan Multiple Range Test were perfomed. The results showed the yeast concentration had a significant effect on water content, ash content, protein content, fat content, carbohydrate content, crude fiber content, color (hedonic and scoring test), taste (hedonic test), texture (hedonic and scoring test), and overall acceptance (hedonic test) and had no effect on the aroma (hedonic test). The result show that the tempeh with a concentration of 5% yeast resulting the best tempeh characteristic with the criteria of 62.64% water content, 0.69% ash content, 9.66% protein content, 3.31% fat content, 23.70% carbohydrate content, 11.13% crude fiber content, color sensory test, aroma, taste, texture, overall acceptance are liked.